Implikasi Pemberlakuan Perubahan Undang-Undang Perkawinan terhadap Permohonan Dispensasi Nikah di Pengadilan Agama Solok - Fadila Rusyda; Syofiarti Syofiarti (LPPM Universitas Ekasakti Padang, 2023)
Act Number (No) 16 of 2019 concerning Amendments to Act Number (No) 1 of 1974 concerning Marriage has been amended in Article 7 regarding the age limit for marriage, which was originally 19 years for men and 16 years for women to 19 years for men and women. The amendment to the law is a follow-up to the decision of the Constitutional Court Number 22/PUU-XV/2017 which was handed down on December 13, 2018. After the revision of the Marriage Law was enacted, the Solok Religious Court experienced a surge in requests for dispensation from marriage. This research is a legal research with descriptive analytical research specifications. The approach used is a normative juridical approach as the main approach, supported by an empirical juridical approach. The data used are primary data as the main data and secondary data as supporting data collected through field studies using interview techniques and literature studies. The data was then analyzed qualitatively and presented in a qualitative descriptive form.